OPTIMASI KESTABILAN KAPAL DENGAN KONTROL FUZZY PADA WATER BALLAST TANK - Imam Sutrisno; Faiq Azhar Taqiyuddin (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Indonesia is a maritime country, and the role of the shipping industry is needed to support the development of the Indonesian economy. The role of this business depends on the industry’s ability to utilize market opportunities that are increasingly wide open. One of them is through the distribution of bulk cargo, which is currently experiencing a fairly rapid increase in line with the increasing development of industry, thus requiring bulk raw materials such as cement, fertilizer, coal, nickel, and other mining materials. Of course, such ships require good ship stability control. Based on this background, research is needed to overcome this problem. In this study, the design of an automatic water ballast tank control and monitoring system is carried out which is expected to be able to achieve sufficient ship stability and prevent excessive ship tilting that can cause accidents in a bulk carrier. With the final result of the ship control and monitoring system research, the GY-6500 sensor can read the tilt with an accuracy of 97.84%, and can restore the ship’s balance within 1 minute and 40 seconds when the ship experiences a moderate tilt of 6 degrees.